Narrativas sobre mujeres migrantes venezolanas en cibermedios de América - Gladys Adriana Espinel-Rubio; Eliana Caterine Mojica-Acevedo; Luis Horacio Botero-Montoya (Mundo Fesc)
Nearly half of all migration movements are led by women, but the representation of migration in the media is male-dominated. At the same time, the emancipation processes of migrant women are complex and often ambivalent due to the dynamics of the context and the intersection of class, gender, and race variables. This research, which emphasizes Venezuelan migration—the second highest in the world, according to the Office of the United Nations High Commissioner for Refugees (UNHCR)—aims to analyze the narratives about Venezuelan migrant women constructed between 2017 and 2021 in five online media outlets in the Americas (four from Latin America and one from the US, written in Spanish). Based on descriptive research and the content and critical discourse analysis method, 494 news articles were explored. Among the main results, it was determined that these narratives focus on prostitution and sexual exploitation. marginalized work; motherhood and health; discrimination and xenophobia, associated with criminal acts committed by and against women. It is concluded that Venezuelan migrant women continue to be rendered invisible, and their representations generate and promote stereotypes, discrimination, and xenophobia in the workplace, social, and cultural spaces among host communities.